New insights into sea ice nitrogen biogeochemical dynamics from the nitrogen isotopes. Issue 2 (25th February 2014) - Fripiat, F.; Sigman, D. M.; Fawcett, S. E.; Rafter, P. A.; Weigand, M. A.; Tison, J.‐L.
Abstract We report nitrogen (N) isotopic measurements of nitrate, total dissolved nitrogen, and particulate nitrogen from Antarctic pack ice in early and late spring. Salinity‐normalized concentrations of total fixed N are approximately twofold higher than in seawater, indicating that sea ice exchanges fixed N with seawater after its formation. The production of low‐δ15N immobile organic matter by partial nitrate assimilation and the subsequent loss of high‐δ15N nitrate during brine convection lowers the δ15N of total fixed N relative to the winter‐supplied nitrate. The effect of incomplete nitrate consumption in sea ice is thus similar to that in the summertime surface ocean, but the degree of nitrate consumption is greater in ice, leading to a higher δ15N for organic N (~3.9‰) than in the open Antarctic Zone (~0.6‰). Relative to previous findings of very high‐δ15N organic matter in sea ice (up to 41‰), this study indicates that it would be difficult for sea ice to explain the high δ15N of ice age Antarctic sediments. The partitioning of N isotopes between particulate and dissolved forms of reduced N suggests that primary production evolved from new to regenerated production from early to late spring. Even though nitrate assimilation raises the δ15N of nitrate, the δ15N of sea ice nitrate is frequently lower than that of seawater, providing direct evidence that the regeneration of reduced N in the ice includes nitrification, with mass and isotopic balances suggesting that nitrification supplies a substantial fraction (up to ~70%) of nitrate assimilated within Antarctic spring sea ice.